Systematic Mapping Study: Political Attitudes in Elections - B RUSLAN, D NUGROHO, M.A SURYADILAGA, MURADI, W.S SUMANDINATA, N.A DELIARNOOR, (Opción, 2019)
This research is to find out what is the impact of political attitudes as a step to conduct a literature review to understand new developments and findings that have emerged in previous studies. A systematic literature review is used in the methodology of this study. As a result, the relationship between competition and efficacy is strongest among citizens with lower levels of education and income. In conclusion, using samples for students that are intended to provide greater heterogeneity and importance in higher education is a great potential for becoming promising candidates for social entrepreneurship